Integrando a Internet das Coisas às Aplicações de TV Digital. - PEREIRA, Danne Makleyston Gomes (2018)
In comparison to the conventional TV, Digital TV allows not only a better image and sound quality but also interactivity and the offering of new services to viewers. On the other hand, the Internet of Things (IoT) is a combination of ubiquitous computing and the Internet, in which IoT devices (e.g., smart objects) can get and exchange data, cooperating with people and the environment in which they are. Many smart objects located in a home can offer features that can be explored to enrich the experience of watching television. However, the convergence between IoT devices and TV applications has several challenges, such as the dynamic discovery of smart objects and the services they provide; the support for the heterogeneity of communication protocols used by smart objects; the identification of viewers and their profiles; the synchronization of the playing media with the smart objects actuators provided in the physical environment; and the need of providing programming abstractions for the development of TV applications that are aware of the smart objects deployed in the physical environment. This work proposes a software architecture, based on a middleware perspective, which allows TV applications to be aware of the physical environment context and interact with it. It also allows the identification of the viewers and their profiles, also providing multi-modal interactions with them and the application running in the digital TV. The proposed software architecture is based on a conceptual model called IoTTV-Ont, also developed as part of this work, that allows the description of a household with smart objects and the people present in it. A prototype that uses a particular implementation of the proposed software architecture was evaluated through use cases, exploring all the requirements specified in this work.